La Gestion D’une Patiente Ayant Hypertension Pulmonaire Thromboembolique Chronique - Haidar, Mohamad Abou; Wehbe, Nancy (European Scientific Journal, ESJ, 2017)
The profession of Physiotherapy has been defined by the "World Confederation for Physical Therapy" (WCPT) as the services provided to individuals and populations to develop, maintain or restore an optimal functioning throughout the life. This includes services facing all the circumstances which may take place and which are caused by the age, musculoskeletal disorders, pain, diseases, disorders, environmental conditions and many other situations. The physiotherapists are thus called upon to identify and maximize the quality of life of individuals by focusing on the promotion of health, the prevention, treatment, intervention and the adaptation or even the rehabilitation. For this, in the clinical environment, the physiotherapist is confronted by a variety of clinical cases which can be very simple or having a level of complexity increased. This project presents a case that can be considered rare but requires the implementation and the integration of multiple skills to be able to manage it. It is a case of pulmonary hypertension chronic thromboembolic which has gone unnoticed for several years and which is complicated by the existence of a sociocultural component which adds to this case an additional challenge when it is supported. The success in the management of this case relies on of the establishment of a good communication with the patient and on the establishment of a relationship of trust which requires of the physiotherapist to detach from social prejudice and to present themselves as an impartial person in dealing with the individuals.